GAMBARAN HIPERTENSI PADA LANSIA DI WILAYAH KERJA PUSKESMAS CUKIR JOMBANG - Athi' Lindayani; Siti Urifah; Edi Wibowo Suwandi (Universitas Pesantren Tinggi Darul Ulum, 2018)
Introduction: Hypertension is one of non-communicable disease and this disease also one of leading killer if they did not get early treatment and early prevention. Mostly Hypertension was among elder people, many factors which influence this disease, such as heredity, eating behavior with high salt, obesity and lowest physical activities. Because of that physical activity like regular exercise can prevent of hypertension complication. The aim of this study was to assess the Progressive Muscle Relaxation (PMR) to reducing high blood pressure among elderly in PHC of Cukir, Jombang.Methodology: the methodology of this reseach used pra experimet with pre-post test desain, the population of this reseach was elderly who had hypertention. 124 respondents was selected by using inclusion criteria. The inclusion criteria are elder people who have hypertension at least six months ago, elderly aged 60 years old or more and elderly who did not consume hypertension medication when attanding this reseach. The data analyzed by t-test with α = 0,05.Results and discussion: the results of this study found that the ages of elederly ranged from 60-75 years old with the mean of 66 years. The majority of elderly were female (72.5%), and more than half of those had elementary school as their highest education (58%) and all of those were Javanese and 64.5% still have work status. The majority (90.4%) participant had hypertension more than 6 months and 70.9% got hypertension from their family history. However, for hypertension level about 56.5% got hypertension level 1, it is systole 140-159 mmHg and diastole 90-99 mmHg. Conclusion:The quality of life and life expectacy of elderly people was special attantion in goverment, because life expectacy is one of indicator for successful national development. Because of that the prevention of degeneratif disease like hypertention is very importance issues among elder people. Keyword : Hipertention, Elderly, Progressive Muscle Relaxation (PMR), Jombang